Math
465 Solution Set 2
Ae Ja Yee
1. If (
a, c
) = 1 and (
b, c
) = 1, then (
ab, c
) = 1.
Solution.
Method 1: Suppose (
ab, c
)
>
1, namely
x

ab
and
x

c
for some
x >
1. Since
(
a, c
) = 1,
x
cannot divide
a
, that is (
x, a
) = 1. However,
x

ab
, so
x

b
, which is a
contradiction.
Method 2: We can write 1 =
ax
1
+
cy
1
=
bx
2
+
cx
2
. Thus
ax
1
bx
2
= (1

cy
1
)(1

cy
2
) = 1

c
(
y
1
+
y
2

cy
1
y
2
)
,
which is equivalent to
1 =
abx
+
cy,
where
x
=
x
1
x
2
and
y
=
y
1
+
y
2

cy
1
y
2
. Therefore, (
ab, c
) = 1.
2
2. Show that if (
a, b
) = 1, then (
a

b, a
+
b
) = 1 or 2. When is the value 2?
Solution.
Method 1: Let
n
=
a

b
,
m
=
a
+
b
, and (
n, m
) =
d
. Then
2
a
=
m
+
n,
2
b
=
m

n
Since (
n, m
) =
d
,
d

2
a
and
d

2
b
, that is
d
is a common divisor of 2
a
and 2
b
. We now
compute (2
a,
2
b
):
(2
a,
2
b
) = 2(
a, b
) = 2
since (
a, b
) = 1. Therefore,
d

2, that is
d
= 1 or 2.
Method 2: Since gcd is the least positive linear combination, (
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
This is the end of the preview.
Sign up
to
access the rest of the document.
 Spring '08
 YEE
 Math, Number Theory, Greatest common divisor, Euclidean algorithm, Binary GCD algorithm, Ae Ja Yee, ab  cbx

Click to edit the document details